Traceable Quantitative Raman Microscopy and X-ray Fluorescence Analysis as Nondestructive Methods for the Characterization of Cu(In, Ga)Se2 Absorber Films. Issue 2 (February 2016) - Zakel, Sabine; Pollakowski, Beatrix; Streeck, Cornelia; Wundrack, Stefan; Weber, Alfons; Brunken, Stefan; Mainz, Roland; Beckhoff, Burckhardt; Stosch, Rainer
The traceability of measured quantities is an essential condition when linking process control parameters to guaranteed physical properties of a product. Using Raman spectroscopy as an analytical tool for monitoring the production of Cu(In1–x Gax )Se2 thin-film solar cells, proper calibration with regard to chemical composition and lateral dimensions is a key prerequisite. This study shows how the multiple requirements of calibration in Raman microscopy might be addressed. The surface elemental composition as well as the integral elemental composition of the samples is traced back by reference-free X-ray fluorescence analysis. Reference Raman spectra are then generated for the relevant Cu(In1–x Gax )Se2 related compounds. The lateral dimensions are calibrated with the help of a novel dimensional standard whose regular structures have been traced back to the International System of Units by metrological scanning force microscopy. On this basis, an approach for the quantitative determination of surface coverage values from lateral Raman mappings is developed together with a complete uncertainty budget. Raman and X-ray spectrometry have here been proven as complementary nondestructive methods combining surface sensitivity and in-depth information on elemental and species distribution for the reliable quality control of Cu(In1-x Gax )Se2 absorbers and Cu(In1-x Gax )3 Se5 surface layer formation.